1986
DOI: 10.1161/01.str.17.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Lobar intracerebral hemorrhage: etiology and a long-term follow-up study of 32 patients.

Abstract: Thirty-two patients with lobar hematoma were encountered during a period of six and a half years. Of these patients, 13 had arterial hypertension, 7 had other etiologies, and the remaining 12 were without apparent etiology. In 5 of these patients, cryptic angiomas were suspected from angiograms and CT scans. In one young patient, there was a later recurrence of hemorrhage that resulted in death. Our experience in this series and a review of the literature have led us to conclude that, in young normotensive pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
2
1

Year Published

1988
1988
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 21 publications
2
14
2
1
Order By: Relevance
“…The frequency of hypertension among patients with lobar ICH was reported to range from 20.0% to 47.5% in the 1980's (Table 6) (1,(15)(16)(17)(18). The frequency of hypertension in lobar ICH (60.0%) in the present study was higher than previously reported.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The frequency of hypertension among patients with lobar ICH was reported to range from 20.0% to 47.5% in the 1980's (Table 6) (1,(15)(16)(17)(18). The frequency of hypertension in lobar ICH (60.0%) in the present study was higher than previously reported.…”
Section: Discussioncontrasting
confidence: 63%
“…The most frequent site was the parietal lobe as reported by Weisberg (16), the occipital lobe by Ropper and Davis (15), the temporoparietal lobes by Kase et al (1), and the temporal or temporoparietal lobes by Tanaka et al (17). In the study by Massaro et al, lobar ICHconfined to one lobe was observed most frequently in the frontal lobe.…”
Section: Discussionmentioning
confidence: 73%
“…This finding is similar to that of previously reported series. 6,9,[11][12][13]15 The most common location of ICH resulting from arteriovenous malformations was lobar. Cavernous angioma was most commonly located supratentorially but was the most common cause of ICH located in the brain stem.…”
Section: Discussionmentioning
confidence: 99%
“…3,7,28,29 One study reported that this association is more significant with lobar ICH. 30 Many studies have reported a high rate of hypertension among cases of ICH, 8,[31][32][33][34][35] and several reported that the rate was not significantly different by location of ICH. 24,35 Few studies have controlled for the presence of other risk factors and demographic variables that may affect the rate of hypertension.…”
Section: Lobar Ichmentioning
confidence: 99%